Carl Sagan : una vida en el cosmos ; traducción, Alfredo Brotons Muñoz ; revisión científico-técnica, David Galadi-Enriquez. - Poundstone, William; Brotons Muñoz, Alfredo; Galadi-Enríquez, David, 1969-; Poundstone, William (Tres Cantos, Madrid, España : Akal, 2017)
A biography of twentieth-century scientist Carl Sagan, discussing his lifelong obsession with interplanetary travel and life in outer space, and considering how that interest made him an icon of popular culture, but reflected badly on his professional standing.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed September 2, 2019)
Keywords: Sagan, Carl, -- 1934-1996.; Astronomers -- United States -- Biography; Biographies; Electronic books